The Fifth Slovene Hamlet: Return to Tradition? - Zlatnar Moe, Marija (Multicultural Shakespeare: Translation, Appropriation and Performance, 2017)
Over the nearly two centuries that Hamlet has been a fixture of the Slovene cultural firmament, the complete text has been translated five times, mostly by highly esteemed figures of Slovene literature and literary translation. This article focuses on the most recent translation, which was done by the prominent Slovene drama translator Srečko Fišer for a performance at the National Theatre in Ljubljana in 2013. It examines the new translation’s relations to its source text as well as to the previous translations. After the late twentieth century, when Hamlet was regarded as a text to be challenged, this new translation indicates the return to the tradition of reverence both for the source text and its author, and for the older translations. This is demonstrated on all levels, from the choice of source text edition, which seems to bear more similarities with the older translations than with the most recent predecessors, to the style, which echoes the solutions used by the earlier translators. Fišer continues the Slovenian tradition to a far greater extent than the two translators twenty years ago, by using the same strategies as the early translators, not fixing what was not broken, and only adding his own interpretation to the existing ones, instead of challenging or ignoring them. At the same time, however, traces of subversion of the source text can be detected, not in the form of rebellion, but rather as a mild disregard. This latest translation is the first one to frequently reshuffle the text. It is also the first to subordinate meaning to style. This all indicates that despite the apparent return to tradition, the source text is no longer treated with the reverence of the past.